Formulation and Activity Testing of Transparent Solid Soap With Ethanol Extract of Pineapple Fruit Peel (Ananas Comosus (L) Merr) Against Staphylococcus Aureus Bacteria - Nurfitria Junita; Irene Otosela Runggamusi (Jurnal Gizi dan Kesehatan Keluarga, 2023)
The pineapple fruit (Ananas comosus (L) Merr) has medicinal properties as a traditional remedy. The pineapple fruit peel is rich in active compounds such as flavonoids, bromelain enzyme, and vitamin C, which are known for their antibacterial properties. This activity is more effective when incorporated into soap formulations. Soap that can kill bacteria is known as antiseptic soap. In this study, the extract of pineapple fruit peel is used to determine whether it can be formulated into a transparent solid soap and to determine the concentration of the extract that meets the requirements for physical evaluation and stability testing of the transparent solid soap formulation. The research is conducted as an experiment by making transparent solid soap. The pineapple fruit peel is extracted using the maceration method with 96% ethanol as the solvent. The obtained extract is then used to create a transparent solid soap formulation with concentrations of 0.5% (F1), 1.0% (F2), and 1.5% (F3) of the pineapple fruit peel extract. This formulation is evaluated through physical evaluation, which includes organoleptic testing, pH testing, foam height testing, water content testing, hardness testing, free alkali number testing, cycling test, and antibacterial activity testing. The antibacterial activity testing shows that all formulations of transparent solid soap with pineapple fruit peel extract can inhibit the growth of Staphylococcus aureus bacteria, with the largest inhibition zone observed in F3 with a diameter of 26.8 mm against Staphylococcus aureus bacteria.